THE BUNHEADS ARE DEAD: Discovering High Tech, High Touch Opportunities in Library and Information Science. - Haycock, Ken; Garner, Carla (Career Planning & Adult Development Journal)
Conjure up a picture of today's librarian, and you are likely to be wrong. Professional librarians are information analysts, freedom of information and protection of privacy officers, family literacy specialists, Internet trainers, teen specialists, genealogists, Web designers and technologists, database managers, historical researchers, information brokers. Indeed, few have the title of “librarian” but all have the master's degree in Library and Information Science (LIS). Graduate LIS programs are appealing to a younger and more diverse student population, yet recruitment is still problematic due to misconceptions about the career and the little-known fact that the first professional degree is at the master's level. For the past several decades, MLIS programs have recognized the morphing of the library from book repository to community information provider, and have redrawn the set of technical skills that go along with the degree. Those who have discovered the contemporary version of the MLIS have been able to dismiss the bunheaded-librarian stereotype traditionally associated with the degree.